Synthesis of coumarin derivatives based fluorescent dye towards the detection of cancer cell - Thinh, Tran Quang; Ha, Tran Thi; Hai, Vu Duy; Hien, Nguyen; Tuan, Mai Anh (Vietnam Journal of Chemistry, 2015)
Fluorescent readout is a powerful technique for the detection of cell cancer. The fluorescent biomarkers (or dyes) should exhibit the ability of the light emission when excited, and the biocompatibility. This work reports on the synthesis of coumarin derivatives based fluorescent dyes. The characterization results, obtained by NMR, HR-MS, absorption and emission spectroscopic method, revealed that these compounds are promising candidates for fluorescent biomarker applications. Keywords. Coumarin derivatives, fluorescence, biomarker, cancer cell, Palladium-catalyzed direct arylation.